Deferral due to low hemoglobin and predictors of permanence in the blood donation system of repeat female blood donors. (June 2022) - Urbina, Adriana; García-Otálora, Michel-Andrés; Mendoza-Romero, Dario; Rocha, Felix; Rodriguez, Ayda; Palomino, Fernando; Weinauer, Franz
Highlights: Low Hb (Hb) is a main cause of blood donor deferral, especially in women. A cohort of 8, 368 repeat female blood donors was followed for seven years. The frequency of low Hb was 0.7–4.1 %, according to baseline Hb concentration. The frequency of low Hb was 5.8–9.1 % in platelet donors and 1.9 % in whole blood donors. The baseline Hb, change in Hb, type of donation, and donation interval are predictors of developing low Hb. Abstract: Objectives: To evaluate the deferral rate due to low hemoglobin (Hb) in repeat female blood donors and identify the factors affecting their permanence in the blood donation system. Materials and methods: 8, 368 repeat female blood donors who donated from January 2012 to December 2018 were included. Bivariate analysis and Kaplan-Meier curves were used to identify the covariates possibly associated with developing low Hb, and Cox proportional hazards modeling was used to adjust for all confounders. Results: The global deferral rate due to low Hb was 2.4 %. According to baseline Hb, the frequency of low Hb was 0.7–4.1 %, and it was higher in platelet donors (5.8–9.1 %) than in whole blood donors (1.9 %). The main predictors were baseline Hb (compared to the first quartile; hazard ratio [HR] = 0.487 for the second quartile; 0.234 for the third; and 0.095 for the fourth); change in Hb (HR = 2.689 for a >0.49 g/dL change, compared to smaller changes); the type of donation (compared to whole blood donors, HR = 2.317 for platelet donors); and donation interval (compared to >12.5 month intervals; HR = 2.220 for 8.0−12.5 months; HR = 5.658 for 5.4−8.0 months; and HR = 9.452 for <5.4 months). Conclusions: In female blood donors at moderate altitude, the probability of developing low Hb increases with a baseline Hb of 13.5−14.0 g/dL, with a change in Hb >0.49 g/dL, in platelet donors, and with donation intervals <12.5 months. These four predictive factors can be used together for early identification of donors at risk of developing low Hb, to institute appropriate measures.